A Review of available treatment methods for polycystic ovary syndrome (PCOS) with special emphasis on diet and physical activity - Cąkała, Marlena; Zajkowska, Aleksandra; Kozioł, Magdalena; Podgórniak, Kamila; Skotnicka, Joanna; Błaszczak, Karolina; Witkowska, Maria (Quality in Sport, 2024)
Polycystic ovary syndrome (PCOS) occurs in 5 to 10% of women of reproductive age and is the most common cause of anovulation in infertile women. PCOS is associated with insulin resistance, type 2 diabetes mellitus, and increased cardiovascular risk. Although insulin resistance is not included as a criterion for diagnosis, it is a critical pathological condition of PCOS. While PCOS can pose challenges to women’s health, with appropriate medical care and lifestyle modifications, symptoms can be effectively managed and the risk of associated health complications reduced. Behavioral, medical and surgical treatments have been evaluated in order to improve the fertility of women with PCOS. Lifestyle modifications (stop smoking, physical exercise and weight loss when necessary) are of the utmost importance. The aim of this paper is to present the available methods of treatment, prevention of consequences and fertility problems affecting women with PCOS.